Genetic evaluation of wild hevea germplasm : early performance - Abraham S T; George P J; Nair R B; Panikkar A O N; Reghu C P (Placrosym XIV, 2000, Hyderabad, India : Programme and Abstracts p.42)
The wild germplasm, is a rich source of many potential genes resistant to various biotic and abiotic stresses. The present study evaluated a set of wild genotypes in a field evaluation trial. The objectives of the study were assessment of the nature and extent of variability present in the wild germplasm, estimation of genetic parameters like heritability and genetic advance and assessment of the yielding trend in the early premature phase. A simple lattice desing with 4 replications and 4 plants per plot was used. The field performance of the genotype was compared with the popular Wickham clone RRII 105. For the morphological characters, the wild genotypes were in general more vigorous than the control in terms of a higher population mean for the girth, height, total number of leaves per plant, total leaf area of the plants and leaf area index. RO/C/9/157 was found to be a very vigorous clone with the maximum mean values for these traits. In the case of dry rubber yield recorded as the average of several test tappings in the third year, the wild genotypes were poor yielders compared to the genetically improved control clone. Howver, one genotype, MT/C/10/24 had a significantly higher test tap yield (4.27 g+ +) than the control (2.35 g ++), while another genotype MT/C/1/91 had a yield (2.09 g ++) on par with the control. Characters like dry rubber yield and certain bark structural characters were found to have high heritability ang high genetic advance indicating their amenability to selection. Several genotypes could be identified as superior for certain important characters like girth, number of leaves, bark thickness, number of latex vessels, diameter of latex vessels besides test tap yield.
Keywords: Genetic evaluation; Hevea germplasm; Wild germplasm